Early Data Show Safety and Efficacy of SAPIEN Pulmonic THV - Nierengarten, Mary Beth (MD Conference Express, 2014)
Early data on the use of the Edwards SAPIEN transcatheter heart valve (THV) for use in the pulmonary position to treat patients with pulmonic disease show excellent clinical outcomes, as well as the durability of the device without stent fractures or the development of endocarditis. This is according to the results of the first 50 patients enrolled in the Congenital Multicenter Trial of Pulmonic Valve Regurgitation Studying the SAPIEN Interventional THV trial [COMPASSION; NCT00676689].